Internal Control Effectiveness, Internal Audit Function, Institutional Complexity, and Audit Opinions as Determinants of Corruption: Evidence from Indonesian Public Sector Institutions - Utomo, Wahyu Setio (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2026)
This study aims to examine the influence of governance mechanisms on corruption cases in Indonesian ministries and government agencies. Specifically, it investigates the effect of internal control effectiveness, internal audit role, institutional size, institutional complexity, and audit opinion on the likelihood of corruption. The study employs a quantitative approach using secondary data collected from official reports published by Komisi Pemberantasan Korupsi, Badan Pemeriksa Keuangan Republik Indonesia, and Badan Pengawasan Keuangan dan Pembangunan over the period 2018–2022. The final sample consists of 405 observations derived from 81 ministries and government agencies selected using purposive sampling. Binary logistic regression is applied to analyze the relationship between the independent variables and corruption cases, which are measured as a dichotomous variable based on finalized legal decisions. The results reveal that internal control effectiveness, internal audit role, institutional size, and institutional complexity have a positive and statistically significant effect on corruption cases. These findings indicate that weaknesses in governance mechanisms and increased organizational scale and complexity are associated with a higher likelihood of corruption. Among the variables, the internal audit role demonstrates the strongest influence, highlighting its critical function in detecting and preventing irregularities. In contrast, audit opinion does not show a statistically significant effect on corruption, suggesting that formal financial reporting assessments may not fully capture underlying corruption dynamics. This finding implies that audit outcomes alone are insufficient to serve as reliable indicators of corruption risk in the public sector. This study contributes to the literature by providing updated empirical evidence on corruption determinants in Indonesian public institutions using recent data and improved variable measurement. The findings offer important policy implications for strengthening governance systems, particularly in enhancing internal control and internal audit effectiveness. Future research is encouraged to incorporate more comprehensive datasets and explore additional governance variables to better understand corruption dynamics.